Non-neutralizing antibodies increase endogenous circulating Ang1 levels. Issue 8 (17th November 2018) - Zheng, Chao; Toth, Joshuaine; Bigwarfe, Tammy; MacDougall, Margit; Jerath, Kavita; Bovat, Kristin; Smith, James; Sun, Peng; Hayes, David; Fryer, Ryan; Singh, Sanjaya; Kroe-Barrett, Rachel
ABSTRACT: Ang1 is a soluble ligand to receptor Tie2, and increasing the circulating Ang1 level may improve vascular stabilization under certain disease conditions. Here, we found that the circulating Ang1 level was significantly increased in cynomolgus monkeys treated with non-neutralizing anti-Ang1 antibodies. Improving the antibodies' pharmacokinetic properties by IgG Fc mutations further increased the circulating Ang1 level. However, the mutations decreased the thermal stability of the molecules, which may limit their use as therapeutic antibodies. Nevertheless, we showed that non-neutralizing antibodies may have therapeutic potential by increasing the level of a target molecule in the circulation.